The protective effect of perceived social support on psychological health during the COVID-19 pandemic: The case of Gyeonggi province in South Korea - Shin, Jeonghoon; Park, Kunhee; Lee, Yubin; Choi, Sojin; Jang, Yeongeun; You, Myoungsoon (Korean Journal of Health Education and Promotion, 2023)
Objectives: This study aims to not only examine the protective role of perceived social support (PSS) but also derive practical implications focusing on its effects on depression and embitterment, while considering negative life events (NLEs) during the COVID-19 pandemic. Methods: An online-based, self-reporting survey was administered in January 2022 to 1,000 community residents that were 18 years of age or older in Gyeonggi province, South Korea. The question items included depression, embitterment, PSS, and NLEs. Some covariates, such as sociodemographic characteristics, justice belief, general and governmental trust, and experience of COVID-19 confirmation and self-isolation, were also included. The hypotheses were examined via a hierarchical regression utilizing bootstrap methods. Results: Higher levels of NLEs during the COVID-19 pandemic are associated with deteriorated levels of depression and embitterment, respectively. The PSS showed significant protective effects on depression and embitterment, respectively, particularly in the consideration of NLEs during the pandemic. The effect of PSS on depression was greater than in that the case of embitterment. Conclusion: From the analysis of Korea, which applies a range of long-term containment strategies, this study highlights the necessity for the government and communities to develop strategies that can reduce the detrimental impact on psychological health vis-à-vis the significant effects of PSS. KCI Citation Count: 0